2013
DOI: 10.1016/j.euroneuro.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain concentrations of citalopram and escitalopram in P-glycoprotein deficient mice after acute and chronic treatment

Abstract: According to both in vitro and in vivo data P-glycoprotein (P-gp) may restrict the uptake of several antidepressants into the brain, thus contributing to the poor success rate of current antidepressant therapies. The therapeutic activity of citalopram resides in the S-enantiomer, whereas the R-enantiomer is practically devoid of serotonin reuptake potency. To date, no in vivo data are available that address whether the enantiomers of citalopram and its metabolites are substrates of P-gp. P-gp knockout (abcb1ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…Future imaging or postmortem studies may offer further information in this regard. Nonetheless, our finding that brain tissue levels of escitalopram were increased three fold by P-gp inhibition compares favorably with recently reported results from studies using P-gp knockout mice, which were published online as this paper was being finalized (Karlsson et al, 2013). Given that it has proven difficult to reproduce effects observed in P-gp knockout mice by P-gp inhibition in the past (Ejsing and Linnet, 2005), it remained vital to demonstrate that P-gp inhibition would result in similarly increased brain levels of escitalopram before proposing that coadministration of a P-gp inhibitor may represent a promising approach to enhance escitalopram delivery to the brain.…”
Section: Discussionsupporting
confidence: 70%
“…Future imaging or postmortem studies may offer further information in this regard. Nonetheless, our finding that brain tissue levels of escitalopram were increased three fold by P-gp inhibition compares favorably with recently reported results from studies using P-gp knockout mice, which were published online as this paper was being finalized (Karlsson et al, 2013). Given that it has proven difficult to reproduce effects observed in P-gp knockout mice by P-gp inhibition in the past (Ejsing and Linnet, 2005), it remained vital to demonstrate that P-gp inhibition would result in similarly increased brain levels of escitalopram before proposing that coadministration of a P-gp inhibitor may represent a promising approach to enhance escitalopram delivery to the brain.…”
Section: Discussionsupporting
confidence: 70%
“…This is expected to be a sufficient amount of time to clear systemic levels of citalopram, which has an estimated half-life of 90 min in mice (Fredricson Overo 1982). Moreover, the dose used in the present study is almost completely eliminated from serum within 6 h (Karlsson et al 2013). One consistently-observed effect of chronic SSRI treatment is the downregulation of 5-HTT availability and function (Benmansour et al 1999; Benmansour et al 2002), which could diminish transporter-mediated release of 5-HT by MDMA.…”
Section: Discussionmentioning
confidence: 92%
“…Blood samples were taken 2 h after drug administration, immediately before the MEG recording, close to the estimated time of peak plasma concentration (Sangkuhl et al , 2011). The relationship between peak plasma and peak CNS levels is complex, but based on animal studies (Cremers et al , 2009; Karlsson et al , 2013) and observed midbrain SERT occupancy in healthy human volunteers (Klein et al , 2006), we expected peak CNS levels over this timeframe. Mean plasma levels after citalopram, measured by a specific validated high performance chromatographic method, were 38.6 ng/ml (range 23.8–55.7 ng/ml) and after placebo, 0 ng/ml.…”
Section: Methodsmentioning
confidence: 99%